ПОДАТКОВИЙ КОНТРОЛЬ У СФЕРІ ВИЯВЛЕННЯ РИЗИКІВ З ПДВ - Ткачик, Федір Петрович; Хома, Христина Андріївна (Науковий журнал «Світ фінансів», 2017)
Ткачик Ф. П., Хома Х. А. Податковий контроль у сфері виявлення ризиків з ПДВ. Досліджено сутність і роль податкових ризиків у системі податкового контролю. Висвітлено основні теоретико-прикладні засади функціонування системи управління податковими ризиками в сфері адміністрування ПДВ. Наведено етапи податкового контролю та методи аналізу рівня податкових ризиків, а також здійснено оцінку діючої системи моніторингу податкових ризиків на мезорівні. Запропоновано основні напрями удосконалення системи податкового контролю в сфері управління податковими ризиками з ПДВ. Ткачик Ф. П., Хома К. А. Налоговый контроль в сфере определения рисков с НДС. Проведено исследование сущности и роли налоговых рисков в системе налогового контроля. Определены основные теоретико-прикладные основы функционирования системы управления налоговыми рисками в сфере администрирования НДС. Исследованы этапы налогового контроля и методы анализа уровня налоговых рисков, а также осуществлена оценка действующей системы мониторинга налоговых рисков на мезоуровне. Предложены основные направления совершенствования системы налогового контроля в сфере управления налоговыми рисками по НДС. Tkachyk F., Khoma Kh. Tax control in the detection of risks with VAT. Introduction. The latest paradigm of economic development of Ukraine is aimed at ensuring stability of income tax payments and filling the budgets of all levels, serving one of the essential conditions for successful social needs. In this context, an important part of the implementation of its functions fiscal authorities is the efficiency of tax control for monitoring the risks of VAT. One way to prevent violations of tax laws is to monitor tax risks. What makes the need for a thorough study of actual problems of control over the work fiscal authorities on tax risk VAT.Purpose. The main goal of the article is to study the modern basic procedures and stage of fiscal control in tax risks of VAT.Results. The article deals with the enrichment research concepts and categories of the tax control system and minimizing tax risks. There was investigated that a significant role is budget – VAT. The article emphasized the need to strengthen the monitoring of the risks of this tax, which coincides with the priority of the State Fiscal Service of Ukraine at this stage. In order to improve control and verification measures prominent role focused to the methodology to determine the risk of business entities that use schemes of tax evasion. It is proved that in most cases, the tax control system provides three main stages of working with VAT tax risks: 1) the early of tax diagnostic (before the deadline for filing declaration of VAT); 2) the electronic control of risks (after the deadline for filing declaration of VAT); 3) the tax control of risks (after the deadline for payment of cash tax liabilities). Detailed analysis became the basis of steps outlined measures to systematize regional fiscal authorities working with schemes of tax evasion.Conclusion. Among the issues in the monitoring system of VAT tax risk should note the need to further improve the automated system to it detect because, as practice shows, often in the category of risky businesses get honest taxpayers. At the same time, minimize tax risks in Ukraine will promote such measures as to provide for compliance with tax and customs legislation, prompt appropriate action against violators of tax laws, further automation the control and revision control and analytical and expert measures of fiscal authorities.